The pathogenesis and therapeutic strategies of heat stroke-induced endothelial injury - Shaokang Wang; Xiaoting Zhang; Yongqi Zhang; Nannan Wu; Lulong Bo; Meitang Wang (Frontiers in Cell and Developmental Biology)
Heat stroke is a severe and life-threatening condition characterized by elevated core body temperature and central nervous system dysfunction, often accompanied by multi-organ damage. The incidence and mortality of heat stroke are increasing due to global warming and more frequent heatwaves. This review aims to summarize the recent progress in understanding the pathogenesis of heat stroke-induced endothelial injury and explore potential therapeutic strategies. The vascular endothelium plays a crucial role in maintaining vascular homeostasis, and its dysfunction is a key factor in the development of heat stroke complications. The pathogenesis of heat stroke-induced endothelial injury involves multiple mechanisms, including degradation of the endothelial glycocalyx, impaired vascular tone regulation, disruption of intercellular junctional proteins, and activation of regulated cell death pathways. Biomarkers such as syndecan-1, endothelin-1, and von Willebrand factor are associated with endothelial injury and can predict disease severity and outcomes. Potential interventions include early fluid resuscitation, heat acclimation, and targeted therapies to inhibit specific cell death pathways or protect the endothelial glycocalyx. Further research is needed to elucidate the detailed mechanisms and develop targeted therapeutic interventions to reduce the morbidity and mortality of heat stroke.